The Maqashid Syariah Perspective on the Implementation of Counselling Services in Addressing Bullying - Teguh Samta Adrian; Nurussakinah Daulay; Abdul Aziz Rusman (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
This study aims to describe the implementation of counselling services in addressing bullying at MAN 2 Deli Serdang and to analyze its relevance from the perspective of maqashid syariah. The research employs qualitative methods, with data collected through observation, interviews, and documentation. The research informants include guidance and counselling teachers, the principal, and the vice-principal. Data were analyzed using the Miles and Huberman approach. The results show that MAN 2 Deli Serdang effectively addresses bullying issues by implementing individual counselling, group guidance, and information services. Individual counselling helps students to open up, understand the reasons behind bullying, and find solutions. Group guidance aims at prevention and intervention, while information services raise awareness about the dangers of bullying. The school also actively engages in bullying prevention and intervention through the education of guidance counsellors, student education, information dissemination, the formation of an Anti-Bullying Task Force, and collaboration with parents, the Ministry of Religion, and the police. The implementation of counselling services at MAN 2 Deli Serdang aligns with the principles of maqashid syariah, particularly in aspects of life protection (hifzh al-nafs), intellect protection (hifzh al-'aql), lineage protection (hifzh al-nasl), honour preservation (hifzh al-'ird), and the creation of welfare (tahqiq al-maslahah) for all school members. This study concludes that the counselling services implemented at MAN 2 Deli Serdang effectively address bullying and are relevant to the principles of maqashid syariah.